Prevelance of obesity among asthmatic patients at Tishreen university Hospital - الخير , محمد; سلمان , ربا; عثمان , صبا (Latakia University Journal -Medical Sciences Series, 2022)
Background: Asthma represents one of the most common chronic disease and is amajor public health problem worldwide. The obesity affects asthma through its effect on the airway, and its release of inflammatory cytokines, that increase the severity of symptoms. Aim:to study the prevelance of obesity among asthmatic patients and to investigate its relationship with asthma control Materials and Methods:this was a cross –sectional study conducted at Tishreen University Hospital,Syria,between June 2020-June 2021-this study included 120 subjects ,divided into three groups: obesity30 (25%),overweight 24(20%)and normal weight 66(55%), their ages varied from 17-62years with a mean age (35,5),there were males 42(35%),female 78(65%),all subjects in the study were submitted to full medical history and clinical examinations ,calculation of body mass index(BMI)and spirometry. SPSS software was used for data analysis, P value <0,05 was considred as statistically significant. Results: the prevelance of obesity among asthmatic patients is 25%, the patients distributed as follows: 68 (56,7%) well controlled, 26 (21,7%) partly controlled and 26(21,7%)uncontrolled, study showed an assossiation between poorer asthma control and Obesity in women but not in men. The FEV1 % Predicted was signficanty lower in the obese than in the non-obese group (p value=0,02) Conclusion: this study showed a high prevalence of obesity in asthmatic patients. a strong assossiation beteween obesity and worse asthma control in women but not in men.